Kreasi Produk Ecoprint Berbasis Kearifan Lokal sebagai Pendukung Persiapan Desa Sumberdem menuju Desa Wisata - Anna Triwijayati; Pieter Sahertian; Zuhkhriyan Zakaria; Didit Prasetyo Nugroho; Bintang Pramudya Putra Prasetya (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2026)
Based on the Decree of the Regent of Malang number 188.45/253/KEP/35.07.013/2023 concerning Tourism Villages in Malang Regency, Sumberdem Village is included in the pioneering category of tourist villages with natural and artificial potential. One of the completeness of a tourist village is the presence of tourist souvenirs, namely culinary, fashion, and crafts. As a pioneering tourist village, Sumberdem Village already has a nature-based thematic village/hamlet and has also developed culinary products such as processed coffee, rosella flowers, lemons, medicinal plants/’empon-empon’, and goat farming, but does not yet fully have craft products as tourist souvenirs. On the other hand, Sumberdem Village has incredibly unique natural potential, namely plants/leaves and flowers, including coffee, papaya, ferns, cloves, ylang-ylang, roses, pine, castor, and so on. These natural materials make ecoprint craft products easy to develop. Based on this situation, the goal of this community service program is to improve the skills of residents in